Effect of photodynamic therapy on the virulence factors of Staphylococcus aureus - Bartolomeu, Maria Manuel Rodrigues (2018)
Staphylococcus aureus are Gram-positive bacteria who integrate the human microbiota. Nevertheless, these bacteria can be pathogenic to the humans. Due to the increasing occurrence of antibiotic-resistant S. aureus new approaches to control this pathogen are necessary. The antimicrobial photodynamic inactivation process (PDI) is based in the combined use of a light source, an oxidizing agent like oxygen and an intermediary agent (a photosensitizer). These three components interact to form cytotoxic reactive oxygen species that irreversibly damage vital constituents of the microbial cells and ultimately lead to cell death. In fact, PDI is being shown to be a promising alternative to the antibiotic approach in the inactivation of pathogenic microorganisms. However, information on effects of photosensitization on particular virulence factors is strikingly scarce. The objective of this work was to evaluate the effect of PDI on virulence factors of S. aureus. For this, as photosensitizer the 5,10,15,20-tetrakis(1-methylpyridinium-4-yl)porphyrin tetra-iodide (Tetra-Py+-Me) and six strains of S. aureus (one reference strain, one strain with 1 enterotoxin, two strains with 3 enterotoxins and two strains resistant to methicillin, MRSA – one with 5 enterotoxins and the other without enterotoxins) were used. The effect of photosensitization on catalase activity, beta hemolysis, lipases, thermonuclease, enterotoxins, coagulase production and resistance to methicillin was assessed. The results indicate that the expression of some virulence factors in the cells subjected to this therapy is affected. Additionally the susceptibility of the strains to PDI did not decrease upon successive treatments.